Spirituality Formation and Example of the Faith of Mary for Prospective Priests and Catholic Youth in Building a Spiritual Life - Gonti Simanullang (Abdimas Paspama, 2023)
Changes in digital culture, individualism, and reduced reflective habits are challenges to the spiritual life of prospective priests and Catholic Young People. Coaching that is only oriented towards the delivery of material is not enough to form prayer discipline, maturity of faith, and commitment to service. This Community Service activity aims to strengthen Christian spirituality through the example of Mary's faith as a person who listens to the Word, obeys God's will, is faithful in suffering, and is ready to serve. The program uses a pastoral-participatory approach through needs identification, seminars, Scripture study, interactive discussions, group sharing, joint prayer, adoration, written reflection, and the preparation of personal commitments. Evaluation is designed through pre-test and post-test, participation observation, reflection rubric, questionnaire, and post-activity monitoring. The draft results showed an increase in average scores from 53.2 to 86.0 in aspects of spiritual understanding, Mary's example of faith, prayer discipline, Scripture reflection, and commitment to service. Qualitative achievements can be seen in the increased ability of participants to relate life experiences with the Word of God, develop prayer habits, and formulate realistic acts of service. The program shows that Mary's example can be used as a framework of formation that integrates the spiritual, human, moral, and pastoral dimensions. Sustainability is directed through prayer groups, periodic mentoring, reflection journals, and active involvement in Church service.